Influence of wastewater type on the impact generated by TiO2 nanoparticles on the oxygen uptake rate in activated sludge process. (1st April 2017) - Cervantes-Avilés, Pabel; Camarillo Piñas, Nayeli; Ida, Junichi; Cuevas-Rodríguez, Germán
Abstract: Physicochemical characteristics of wastewater have a relationship with the stability of TiO2 nanoparticles (NPs). This in turn has an effect on the toxicity of TiO2 NPs in microorganisms. In this work, the effect of TiO2 NPs on activated sludge process was evaluated using three different types of wastewater: synthetic, raw, and filtered. The results showed that aggregate size of TiO2 NPs and their specific adsorption of substrates were influenced by the type of substrates and the presence of suspended solids in the wastewater. It was also shown that TiO2 NPs in raw wastewater severely inhibited oxygen uptake by microorganisms as compared to uptake in synthetic or filtered wastewater. The attachment of TiO2 NP aggregates on cell membranes was observed for all types of wastewater. However, the internalization of TiO2 NPs by microorganisms was observed only for raw and filtered wastewater. These results indicate that the effects caused by TiO2 NPs on activated sludge were different depending on the wastewater used for the experiment. Highlights: Aggregates size of TiO2 NPs was related with the adsorption of CODs in wastewater. TiO2 NPs inhibited the oxygen uptake in the activated sludge process. The Inhibition caused by TiO2 NPs depended of substrates type and TSS in wastewater. TiO2 NPs altered microorganisms by membrane cell disruption and internalization. The effects of TiO2 NPs in biological WWTP must be evaluated by using raw wastewater.